Is Lifelong Knee Joint Force from Work, Home, and Sport Related to Knee Osteoarthritis? - Ratzlaff, Charles R. (Hindawi Publishing Corporation, 2012)
Purpose. To investigate the association of cumulative lifetime knee joint force on the risk of self-reported medically-diagnosed knee osteoarthritis (OA). Methods. Exposure data on lifetime physical activity type (occupational, household, sport/recreation) and dose (frequency, intensity, duration) were collected from 4,269 Canadian men and women as part of the Physical Activity and Joint Heath cohort study. Subjects were ranked in terms of the “cumulative peak force index”, a measure of lifetime mechanical knee force. Multivariable logistic regression was conducted to obtain adjusted effects for mean lifetime knee force on the risk of knee OA. Results. High levels of total lifetime, occupational and household-related force were associated with an increased in risk of OA, with odds ratio's ranging from approximately 1.3 to 2. Joint injury, high BMI and older age were related to risk of knee OA, consistent with previous studies. Conclusions. A newly developed measure of lifetime mechanical knee force from physical activity was employed to estimate the risk of self-reported, medically-diagnosed knee OA. While there are limitations, this paper suggests that high levels of total lifetime force (all domains combined), and occupational force in men and household force in women were risk factors for knee OA.